Rockwood & Wilkins' fractures in children - Flynn, John M.; Skaggs, David L.; Waters, Peter M. (Philadelphia : Wolters Kluwer Health, 2015)
"For the gold-standard resource on pediatric fractures, reach for Rockwood and Wilkins' Fractures in Children. Written by leading orthopaedic surgeons from around the world, the revised and expanded 8th edition of this classic bestselling text presents complete, up-to-date coverage of all types of children's fractures. A must-read for pediatric orthopedic surgeons and orthopedic residents. Features: NEW expanded coverage of pain medicine and casting; NEW 6 new authors from around the world; NEW time-saving outline template for easy quick-reference. Step-by-step instructions and expert guidance on numerous operative and management techniques. Author's Preferred Technique section includes algorithms explaining why the author chose that procedure. Pearls and Pitfalls and preventive measures listed for all procedures. NEW 13 full length procedural videos. Casting, remodeling and unique features of children's fractures. Now with the print edition, enjoy the bundled interactive eBook edition, offering tablet, smartphone, or online access to: Complete content with enhanced navigation, A powerful search that pulls results from content in the book, your notes, and even the web, Cross-linked pages, references, and more for easy navigation, Highlighting tool for easier reference of key content throughout the text, Ability to take and share notes with friends and colleagues, Quick reference tabbing to save your favorite content for future use, 13 full length procedural videos"--Provided by publisher.
Epidemiology of fractures in children -- The immature skeleton -- Pain management and procedural sedation for the injured child -- Cast and splint immobilization, remodeling and special issues of children's fractures -- Management of the multiply injured child -- Compartment syndrome in children -- Physeal injuries and growth disturbances -- Pathologic fractures -- The orthopedic recognition of child maltreatment -- Fractures and dislocations of the hand and carpal bones in children -- Fractures of the distal radius and ulna -- Diaphyseal radius and ulna fractures -- Radial neck and olecranon fractures -- Monteggia fracture-dislocation in children -- Evaluation of pediatric distal humeral fractures -- Supracondylar fractures of the distal humerus -- T-condylar distal humerus fractures -- Dislocations of the elbows, medial epicondylar humerus fractures -- Lateral condylar and capitellar fractures of the distal humerus -- Distal humeral physeal, medial condyle, lateral epicondylar, and other uncommon elbow fractures -- Humeral shaft and proximal humerus, shoulder dislocation -- Clavicle and scapula fractures: acromioclavicular and sternoclavicular injuries -- Cervical spine injuries in children -- Thoracolumbar spine fractures -- Pelvic and acetabular fractures -- Fractures and traumatic dislocations of the hip in children -- Femoral shaft fractures -- Fractures of the distal femoral physis -- Proximal tibial physeal fractures -- Intra-articular injuries of the knee -- Fractures of the shaft of the tibia and fibula -- Ankle fractures -- Fractures and dislocations of the foot.
Preceded by: Rockwood and Wilkins' fractures in children / editors, James H. Beaty, James R. Kasser. 7th edition c2010.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Fractures in children; Fractures; Dislocations; Infants; Electronic books